1953
DOI: 10.1161/01.res.1.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Amines in Experimental Hypertensions

Abstract: A sympathomimetic amine, Paredrine, was shown to be a good antihypertensive agent in experimental renal, experimental neurogenic and spontaneous hypertensions in the dog. Other closely related amines failed to possess antihypertensive activity. Paredrine did not prevent the development of experimental renal hypertension. This amine was also without chronic effect on the blood pressure of normotensive dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1953
1953
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Another possible explanation implies that APLs stimulate the immune system in order to regulate the MS related T-cells [23]. Two phase II trials using an APL designed based on the human immunodominant MBP [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] peptide have been reported [24,25]. Both were stopped prematurely due to hypersensitivity reactions in one and disease exacerbation in the other.…”
Section: Linear and Cyclic Apls Against Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible explanation implies that APLs stimulate the immune system in order to regulate the MS related T-cells [23]. Two phase II trials using an APL designed based on the human immunodominant MBP [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] peptide have been reported [24,25]. Both were stopped prematurely due to hypersensitivity reactions in one and disease exacerbation in the other.…”
Section: Linear and Cyclic Apls Against Msmentioning
confidence: 99%
“…In an attempt to correlate the antagonistic activity of linear APLs of MBP [87][88][89][90][91][92][93][94][95][96][97][98][99] with their conformation, full molecular dynamics studies of their complexes with HLA-DR2b in aqueous solvent have been performed [36]. It was found that once bound to the MHC, significant changes occur in the orientation of the amino acids that serve as TCR anchors, compared to their conformation in solution.…”
Section: Linear and Cyclic Apls Against Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Parahydroxyamphetamine (HANNA, 1960;SCHMITT and SCHtvIlTT, 1970;VALETTE et al, 1971), and phydroxynorephedrine (SCHl\lITT and SCHMITT, 1970;VALETTE et al, 1971) have been shown to have pressor effects in several animal species. However, p-hydroxyamphetamine has antihypertensive effects in addition to pressor effect under certain conditions (OHLER and WAKERLIN, 1953). It may be suggested that the delayed antihypertensive effect might be due to the depletion of NA and incorporation of phydroxynorephedrine into peripher al or central NA neurons.…”
Section: :) the Pressor Responsementioning
confidence: 99%
“…This possibility is given credence by evidence of impaired adrenergic neuron function after moderate to large doses of amphetamine (1). Also, p-hydroxyamphetamine (PHA), the intermediary metabolite in the conversion of amphetamine to PHN, has similarly been shown to suppress reflex sympathetic function in normotensive human (4) and to lower the blood pressure (BP) in hypertensive dogs (5).…”
Section: Introductionmentioning
confidence: 99%